PsycEXTRA Dataset 2013
DOI: 10.1037/e578482014-171
|View full text |Cite
|
Sign up to set email alerts
|

Non-offending mothers of sexually abused children: How they decide whom to believe

Abstract: perspective, and good humor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Understanding the most common theories can help underscore where more research may be needed and what theories researchers might want to expand on in their future work. Attachment theory is the most commonly cited by studies qualitative literature on this topic (Bellhouse, 2013; Coles, 2006; Fisher, 2000; Harris, 2008; Hooper & Koprowska, 2004; Koren-Karie et al, 2004; Kreklewetz, 1995; Lasiuk, 2007; Lev-Wiesel, 2006; McCoy, 2014; McMillan, 2013; O’Brien, 1998; Palmer, 2004; J. Walker, 2007a; Williams, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the most common theories can help underscore where more research may be needed and what theories researchers might want to expand on in their future work. Attachment theory is the most commonly cited by studies qualitative literature on this topic (Bellhouse, 2013; Coles, 2006; Fisher, 2000; Harris, 2008; Hooper & Koprowska, 2004; Koren-Karie et al, 2004; Kreklewetz, 1995; Lasiuk, 2007; Lev-Wiesel, 2006; McCoy, 2014; McMillan, 2013; O’Brien, 1998; Palmer, 2004; J. Walker, 2007a; Williams, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These aforementioned signs and symptoms revealed by Myrick and Green ( 2013 ) are supported by Tavkar and Hansen ( 2011 :189), who reported that mothers of SAC expressed significant levels of distress following CSA disclosure. They experienced elevated levels of stress, but a variety of distress symptoms were seen as evidenced by the mothers being restless (McMillan 2013 ).…”
Section: Introductionmentioning
confidence: 99%